2015
DOI: 10.4162/nrp.2015.9.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy knowledge, perception of food allergy labeling, and level of dietary practice: A comparison between children with and without food allergy experience

Abstract: BACKGROUND/OBJECTIVESThe prevalence of food allergies in Korean children aged 6 to 12 years increased from 10.9% in 1995 to 12.6% in 2012 according to nationwide population studies. Treatment for food allergies is avoidance of allergenic-related foods and epinephrine auto-injector (EPI) for accidental allergic reactions. This study compared knowledge and perception of food allergy labeling and dietary practices of students.SUBJECTS/METHODSThe study was conducted with the fourth to sixth grade students from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
14
1
3
Order By: Relevance
“…Skin manifestations were also the most frequently stated symptoms in similar studies conducted in Taiwan, Korea. 9,38 Other symptoms also being noticed among the respondents were itching on the throat about 7.9%, vomiting tendency 4.3%, hives 5.9% and dyspnoea 4.1%. A study conducted in Lebanon, 86% of the food allergy sufferers suffered from skin reactions, including hives, itching, and redness and 30% reported facial swelling.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Skin manifestations were also the most frequently stated symptoms in similar studies conducted in Taiwan, Korea. 9,38 Other symptoms also being noticed among the respondents were itching on the throat about 7.9%, vomiting tendency 4.3%, hives 5.9% and dyspnoea 4.1%. A study conducted in Lebanon, 86% of the food allergy sufferers suffered from skin reactions, including hives, itching, and redness and 30% reported facial swelling.…”
Section: Discussionmentioning
confidence: 93%
“…7 angioedema, dermatitis, as well as in the gastrointestinal tract including vomiting, abdominal cramping, nausea, diarrhea and in the respiratory tract disorder including rhinitis, asthma, laryngeal edema. [8][9][10][11] Anaphylactic shock is the most frightening symptom which is induced by a particular food that is acute in onset, occurring within minutes or hours, and without proper treatment, it may lead to death badly. 12,13 Much other allergic disorder has been found in different organ systems that increase the risk of other allergic condition due to consuming allergic food items.…”
Section: Introductionmentioning
confidence: 99%
“…However, employees should have full knowledge of allergies when developing foods, and thus in-depth and detailed research is needed for overall improvements as reported in other studies on nutrition labeling [ 45 , 46 ]. Studies on allergy labeling are rare in Korea except for a study on adolescents by Choi et al [ 47 ]. Therefore, labeling of allergenic foods should be made easier and more convenient for employees, developers, and consumers.…”
Section: Discussionmentioning
confidence: 99%
“…У детей младшего возраста формируется пожизненная сенсибилизация к белкам коровьего молока [28]. Диагноз аллергии на пищевой белок, в том числе белок коровьего молока, устанавливается на основании данных семейного анамнеза, результатов осмотра и лабораторных исследований с проведением кожных тестов и/или определением уровня специфических IgEантител в сыворотке крови [26,29].…”
Section: аллергия на белок коровьего молокаunclassified